2012
DOI: 10.3899/jrheum.111470
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Vascular Cell Adhesion Molecule, But Not Neutrophil Gelatinase-associated Lipocalin, Is Associated with Lupus Nephritis

Abstract: Objective Vascular cell adhesion molecule-1 (VCAM-1), an adhesion molecule, is involved in the progression of glomerular and tubulointerstitial injury. Neutrophil gelatinase-associated lipocalin (NGAL), a member of the lipocalin superfamily, has been shown to rise in both acute and chronic kidney damage. Both VCAM-1 and NGAL have been found at high levels in the urine of patients with active lupus nephritis. We investigated both as potential biomarkers for lupus nephritis. Methods VCAM-1 and NGAL were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 38 publications
(50 reference statements)
6
54
1
Order By: Relevance
“…It also functions in leukocyte‐endothelial cell signal transduction, and plays a role in the development of atherosclerosis and various autoimmune diseases, including SLE, rheumatoid arthritis, Sjögren's syndrome and vasculitis . Several studies have reported that serum and urinary VCAM‐1 correlate significantly with overall disease activity and damage scores in SLE, as well as with LN . It is also a good marker of renal disease in murine lupus …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also functions in leukocyte‐endothelial cell signal transduction, and plays a role in the development of atherosclerosis and various autoimmune diseases, including SLE, rheumatoid arthritis, Sjögren's syndrome and vasculitis . Several studies have reported that serum and urinary VCAM‐1 correlate significantly with overall disease activity and damage scores in SLE, as well as with LN . It is also a good marker of renal disease in murine lupus …”
Section: Discussionmentioning
confidence: 99%
“…It also functions in leukocyte‐endothelial cell signal transduction, and plays a role in the development of atherosclerosis and various autoimmune diseases . Many studies have suggested that serum and urinary levels of soluble VCAM‐1 significantly correlate with overall disease activity and damage scores in SLE, as well as with LN . Our previous study documented that urinary VCAM‐1 was increased in SLE patients, and correlated with renal activity and SLE Disease Activity Index (SLEDAI) scores …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Urinary NGAL has previously been shown to be a useful predictor of impending flare in both the UK JSLE Cohort [26] and in an adult SLE study of the ELC which included a University College London validation cohort [43]. Kiani et al were also unable to detect an association between urinary NGAL and LN in a prospective study that included 107 adult SLE patients [44]. These observations may be due to urinary NGAL levels peaking before flares and then receding before the event becomes clinically detectable [45].…”
Section: Discussionmentioning
confidence: 99%
“…121 VCAM-1 plays a role in tethering leukocytes, which are drawn to sites of inflammation, to endothelial cells. 122 Urinary VCAM-1 has been shown in several studies of human disease to be strongly correlated with LN activity and severity 77,123,124 in LN. Serum levels of VCAM have previously been shown to correlate with the severity of LN, being highest in WHO Class III and IV, versus inactive or mild nephritis (WHO Class I or II), 125 and levels diminished with treatment.…”
Section: Types Of Ln Biomarkersmentioning
confidence: 99%